Respuesta :
Answer:
y-6 = -7(x-3)
Step-by-step explanation:
[tex]y-y_{1} =m(x-x_{1})[/tex]
y - 6 = m(x - 3)
[tex]m = \frac{-8-6}{5-3}=\frac{-14}{2}=-7[/tex]
y-6 = -7(x-3)
Answer:
y - 6 = -7(x - 3)
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
Algebra I
Slope Formula: [tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]
Point-Slope Form: y - y₁ = m(x - x₁)
- x₁ - x coordinate
- y₁ - y coordinate
- m - slope
Step-by-step explanation:
Step 1: Define
Point (3, 6)
Point (5, -8)
Step 2: Find slope m
- Substitute: [tex]m=\frac{-8-6}{5-3}[/tex]
- Subtract: [tex]m=\frac{-14}{2}[/tex]
- Divide: [tex]m=-7[/tex]
Step 3: Write equation
Point (3, 6)
Slope m = -7
y - 6 = -7(x - 3)